Latvijas sporta klubu tīmekļa vietņu kvalitāte - Gladinovs, Andris (Latvijas Universitāte, 2013)
Bakalaura darba pētījums ir par Latvijas sporta klubu tīmekļa vietņu kvalitāti. Darba autors pēta 18 Latvijas basketbola, futbola un hokeja sporta klubu tīmekļa vietnes. Katra sporta kluba tīmekļa vietne tika pētīta balstoties uz 20 kvalitātes kritērijiem: dizaina noformējums, multimēdiju iekļaušana, saprotama sadaļu navigācija u.c. Lai labāk izprastu sporta klubu tīmekļa vietņu lietototāju viedokli, autors anketēja 57 sporta pasākumu atbalstītājus. Visi anketas dati skaitliski ir atspoguļoti tabulās un diagrammās. Pielikumā trijās tabulās ir pievienoti visu pētāmo sporta klubu tīmekļa vietņu rezultāti. Atslēgvārdi: sporta klubi, futbols, basketbols, hokejs, tīmekļa vietņu kvalitāte -

This bachelor’s paper investigates the quality of Latvian sport club web pages. The author researched 18 Latvian top league playing football, basketball and ice-hockey teams, which are included in the local and official sport federations web pages. Each sport club web page has been researched using 20 specific quality criterias, amongst them: web page design, multimedia inclusion, understandable web page navigation system u.c). To understand user satisfaction with Latvian sport club web pages, the author questioned 57 sport fans from the local basketball, football and ice-hockey games. All numerical results obtained from the research questionnaire are presented in tables and graphics. All researched Latvian sport club web page results are also presented in three compact tables in the Appendix section. Keywords: sport clubs, football, basketball, ice-hockey, web page quality -
The quality of Latvian sport club home pages
Keywords: Bibliotēkzinātne